Penyelesaian Sengketa Pelepasan Hak Atas Tanah Oleh Pemerintah Dalam Proses Pendaftaran Tanah - T. Surya Reza (Prodi Tata Negara (Siyasah) IAIN Langsa, 2021)
Article 41 paragraph (2) of Law No. 2 of 2012 on Land Procurement for Development in the Public Interest states that, when granting Compensation of Parties Entitled to receive Mandatory Compensation, a. exercising the release of rights; and b. submit evidence of ownership or ownership of Land Procurement Objects to Agencies that require land through land institutions. In the court's ruling stated that the boundaries of the land should be mentioned and how much extent was waived and the rest how much, and the procedure of disengagement of the right there was preparation, planning, implementation and release, and the release of the land rights was always followed by compensation, because this is an unlawful act. The results of this study show that, the release of land rights by the government in the land registration process in the court's ruling states that if 6 (six) landowners relinquish the right, it must be 6 (six) people who relinquish their rights if only 2 (two) are invalid, then a new land is said to be state land after the release of his rights. Any release of land rights must have a reason there can't be no reason land is being released to the state. The procedure for the release of that right is there is preparation, planning, implementation and release, and the release of the land rights is always followed by compensation.